Implantable silicon neural probes with nanophotonic phased arrays for single-lobe beam steering - Fu-Der Chen; Ankita Sharma; Tianyuan Xue; Youngho Jung; Alperen Govdeli; Jason C. C. Mak; Homeira Moradi Chameh; Mandana Movahed; Michael G. K. Brunk; Xianshu Luo; Hongyao Chua; Patrick Guo-Qiang Lo; et al. (Communications Engineering)
Abstract In brain activity mapping with optogenetics, patterned illumination is crucial for targeted neural stimulation. However, due to optical scattering in brain tissue, light-emitting implants are needed to bring patterned illumination to deep brain regions. A promising solution is silicon neural probes with integrated nanophotonic circuits that form tailored beam patterns without lenses. Here we propose neural probes with grating-based light emitters that generate a single steerable beam. The light emitters, optimized for blue or amber light, combine end-fire optical phased arrays with slab gratings to suppress higher-order sidelobes. In vivo experiments in mice demonstrated that the optical phased array provided sufficient power for optogenetic stimulation. While beam steering performance in tissue reveals challenges, including beam broadening from scattering and the need for a wider steering range, this proof-of-concept demonstration illustrates the design principles for realizing compact optical phased arrays capable of continuous single-beam scanning, laying the groundwork for advancing optical phased arrays toward targeted optogenetic stimulation.